2013
DOI: 10.1089/neu.2012.2606
|View full text |Cite
|
Sign up to set email alerts
|

S100B Protein May Detect Brain Death Development after Severe Traumatic Brain Injury

Abstract: Despite improvements in the process of organ donation and transplants, the number of organ donors is progressively declining in developed countries. Therefore, the early detection of patients at risk for brain death (BD) is a priority for transplant teams seeking more efficient identification of potential donors. In the extensive literature on S100B as a biomarker for traumatic brain injury (TBI), no evidence appears to exist on its prognostic capacity as a predictor of BD after severe TBI. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 50 publications
3
29
1
4
Order By: Relevance
“…Nevertheless, the obtained results seemed to be interesting enough that it was decided to present them in the form of a preliminary report. Third, in the present study, a single measurement of serum S100B protein concentration was used; previous publications showed that the concentration of that protein differs over time after an injury [7,14]. Finally, serum S100B protein concentration correlates with scores in the GOS scale [6]; thus, the difference between the studied group and the control subjects could result at least partially from that fact.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Nevertheless, the obtained results seemed to be interesting enough that it was decided to present them in the form of a preliminary report. Third, in the present study, a single measurement of serum S100B protein concentration was used; previous publications showed that the concentration of that protein differs over time after an injury [7,14]. Finally, serum S100B protein concentration correlates with scores in the GOS scale [6]; thus, the difference between the studied group and the control subjects could result at least partially from that fact.…”
Section: Discussionmentioning
confidence: 85%
“…Similar results were obtained by Egea-Gurererro et al in patients after severe brain damage with brain death confirmation; with a cut-off point of 2.0 µg L -1 , the value of the AUROC was 0.92 with a specificity of 100%, a sensitivity of 60% and an odds ratio of OR = 8.38 [12]. In previous studies with lower cut-off thresholds (0.365 µg L -1 [13], 0.372 µg L -1 [14]), the diagnostic accuracy was also lower (0.75 [13] and 0.78 [14], respectively). In a meta-analysis involving 39 cohort studies, the cut-off point for death prediction (with a specificity of 100%) ranged from 1.38 to 10.50 µg L -1 , and for predicting impaired neurological state (GCS ≤ 3 points), the cut-off point ranged from 2.16 to 14 µg L -1 [5].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…6 In patients with minor brain injury ( MBI) 7 as well as in patients with severe brain injury, a significant correlation between S100B levels and an unfavourable outcome was identified. 8,9 There are contradictive reports on the expression of S100B in different types of TBI: S100B proteins were reported at high levels in cerebrospinal fluid (CSF) after subarachnoid hemorrhage (SAH). 10 Biberthaler et al 4 reported highest levels of S100B in patients with epidural hematomas, followed by subdural, subarachnoid hemorrhage and brain contusions, whereas in another study, S100B levels in patients with epidural hematomas were shown to be normal.…”
Section: Introductionmentioning
confidence: 99%
“…It may be possible to use S100B as a biomarker of brain injury if measured immediately after injury; however, most mild brain injury patients are not evaluated at the time the injury occurs (Guingab-Cagmat et al, 2013). S100B levels in blood at 24 h post-traumatic brain injury provides an early and sensitive biomarker for the prediction of brain damage which may be useful in defining early risk patterns (Egea-Guerrero et al, 2013). Elevated serum levels of S100B correlate with MRI abnormality and neuropsychological examination after mild traumatic brain injury (Ingebrigtsen et al, 1999).…”
Section: Neuron-specific Enolase (Nse)mentioning
confidence: 99%